Radiographic and Clinical Evidence for Osteoarthritis at Medium-Term Follow-up after Arthroscopic Partial Medial Meniscectomy. (December 2021) - Lamplot, Joseph D.; Tompkins, William P.; Friedman, Michael V.; Nguyen, Joseph T.; Rai, Muhammad Farooq; Brophy, Robert H.
Objective: The purpose of this study is to assess if incident radiographic osteoarthritis (OA) is associated with clinical OA symptoms at midterm follow-up after arthroscopic partial medial meniscectomy (APMM). Design: A total of 44 patients (43% females, mean age 50.1 ± 2.8 years, minimum 5.6-year follow-up) with isolated medial meniscal tears and no-to-mild preoperative radiographic OA underwent APMM. Incident radiographic OA was assessed using the modified Kellgren-Lawrence (K-L) classification. Patients completed the Knee Injury and Osteoarthritis Outcomes Score (KOOS), and subscale thresholds for assessment of a symptomatic knee (KOOS OA criteria) and for Patient non-Acceptable Symptom State (PASS-N) following anterior cruciate ligament reconstruction (ACL-R) were calculated. Results: Incident medial compartment OA occurred in 50% of patients. Morbidly obese patients (body mass index ≥35 kg/m 2 ) were more likely to demonstrate incident radiographic OA (100% vs. 41%, P = 0.002). Forty-three percent of patients met KOOS OA criteria, while 77% were PASS-N. Females were more likely to meet KOOS OA criteria (73% vs. 21%, P = 0.009). Patients with incident radiographic OA in any compartment were more likely than those without radiographic OA to meet KOOS OA criteria (71% vs. 17%, P = 0.008). Patients with preoperative K-L grade 2 changes in any compartment were more likely to meet KOOS OA criteria than those without K-L grade 2 changes in any compartment (83% vs. 35%, P = 0.037). Conclusions: Roughly half of APMM patients will have incident radiographic OA within 6 years of APMM, and this risk increases with obesity. Females and patients with incident radiographic OA are more likely to meet clinical thresholds for OA.